30 Memorable: medication management in older people: realist approaches based on literature and evaluation. (20th August 2018) - Maidment, Ian; Booth, Andrew; Lawson, Sally; Bailey, Sylvia; McKeown, Jane; Zaman, Hadar; Mullan, Judy; Wong, Geoff
Abstract : Objectives: Older people are major users of medication. Their use of medication is increasing, over the last 20 years the number older people taking at least 5 medicines has quadrupled to nearly 50%. They should be taking medication that gives them more benefits than harms. As people get older or their health changes, the balance between benefits and harms for the medication they take will likely change. Medication management by health care practitioners (e.g. pharmacists, doctors and nurses) if done well is a process that can help older people decide if they need to be on certain medications – thus potentially helping to address the issue of over-treatment. However current evidence indicates that medication management is a complex process that is not easy to do well. The objective of the MEMORABLE project, which is funded by the NIHR, is to understand how medication management works and how it might be implemented effectively. Method: This project uses a realist approaches to understand how, why, for whom and in what circumstances medicines management works. These are theory-driven ways to make sense of primary and secondary data, and are suited to making sense of complex interventions, such as medicines management, where outcomes are context sensitive. MEMORABLE uses secondary data from the literature and primary data from up to 60 interviews with older people, carers and practitioners. Data will be synthesised within and across both datasets to set out and refine programme theories, about how medication management works. The findings will be developed into a framework, including guidance and recommendations, to improve practice. Results: We have identified from the literature and interviews: – 3 candidate programme theories, one each relating to older people, their informal carers and care practitioners, which are being drafted and refined. These programme theories will be explored against a six stage process, conceived as a framework for analysis of the literature and interview data. The six stage process is set out below: 1. Identifying the problem. 2. Obtaining medication. 3. Starting medication. 4. Continuing to take medication. 5. Reviewing medication. 6. De-prescribing (stopping inappropriate medication). – Emerging mechanisms of interest, trust, needs/concerns, dissonance are being explored. Conclusions: MEMORABLE, which started in May 2017 and ends in December 2018, is using an innovative methodology, applied collaboratively, to develop an outcome-focused, evidence/experience-based framework to support and enhance medication management. This framework will be meaningful and relevant to those involved in the care of older people, as well as the wider community of interest.